Stroke Repair via Biomimicry of the Subventricular Zone - Matta, Rita; Gonzalez, Anjelica L. (Frontiers in Materials, 2018)
Stroke is among the leading causes of death and disability worldwide, 85% of which are ischemic. Current stroke therapies are limited by a narrow effective therapeutic time and fail to effectively complete the recovery of the damaged area. Magnetic resonance imaging of the subventricular zone (SVZ) following infarct/stroke has allowed visualization of new axonal connections and projections being formed, while new immature neurons migrate from the SVZ to the peri-infarct area. Such studies suggest that the SVZ is a primary source of regenerative cells for the repair and regeneration of stroke-damaged neurons and tissue. Therefore, the development of tissue engineered scaffolds that serve as a bioreplicative SVZ niche would support the survival of multiple cell types that reside in the SVZ. Essential to replication of the human SVZ microenvironment is the establishment of microvasculature that regulates both the healthy and stroke-injured blood brain barrier, which is dysregulated post-stroke. In order to reproduce this niche, understanding how cells interact in this environment is critical, in particular neural stem cells, endothelial cells, pericytes, ependymal cells, and microglia. Remodeling and repair of the matrix-rich SVZ niche by endogenous reparative mechanisms may then support functional recovery when enhanced by an artificial niche that supports the survival and proliferation of migrating vascular and neuronal cells. Critical considerations to mimic this area include an understanding of resident cell types, delivery method, and the use of biocompatible materials. Controlling stem cell survival, differentiation, and migration are key factors to consider when transplanting stem cells. Here, we discuss the role of the SVZ architecture and resident cells in the promotion and enhancement of endogenous repair mechanisms. We elucidate the interplay between the extracellular matrix composition and cell interactions prior to and following stroke. Lastly, we review current cell and neuronal niche biomimetic materials that allow for a tissue- engineered approach in order to promote structural and functional restoration of neural circuitry. By creating an artificial mimetic SVZ, tissue engineers can strive to facilitate tissue regeneration and functional recovery.